PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS DIMEDIASI KEPUASAN KONSUMEN PADA PT. JNE SURABAYA - Andrianto, Rifky Reza (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out that service quality has direct influence to the customer loyalty or it is mediated by satisfaction. The population is the customer who has ever used goods delivery service at PT JNE Surabaya. The sample collection has been carried out by using non probability sampling and the samples are 100 people. Path analysis method is used as analysis technique is using. The result of the test shows the influence of service quality and customer satisfaction each of them has significant influence to the customer loyalty that has ever used goods delivery service at PT JNE Surabaya. Likewise, service quality to the customer satisfaction shows significant influence. This condition can be concluded that service quality can have direct influence to the customer loyalty that uses goods delivery service at PT JNE Surabaya or can have indirect influence through the satisfaction as the intervening variable, and then it influences their loyalty.Keywords: Service Quality, Loyalty, Satisfaction.